COMPUTER AND A CHILD WITH AUTISM - VANKOVA, Jirina; BEDNARIKOVA, Anna (Trends in education, 2014)
Educational computer activities can be an appropriate way to shape and develop skills of a child with autism in the area of sensory perception and imagination, fine motor skills and communication and social interaction. Computer games and educational programs have been taken from the websites, we wanted to highlight their functionality when working with children.
Keywords: autism; computer; computer games; iPAD.